Глава 3.7. Особливості судового розгляду цивільних справ про стягнення аліментів на утримання малолітніх та неповнолітніх дітей та примусове виконання судових рішень по даних справах - Татулич, Ірина Юріївна; Сплавська , Ірина Корніївна (Цивільний та виконавчий процес: міжгалузеві зв’язки. Особливості розгляду судами певних категорій справ та виконання судових рішень. Монографія, 2024)
The article analyzes the peculiarities of judicial consideration of civil cases on recovery of alimony for young and minor children, as well as the enforcement of court decisions and court orders in these cases. The legislation regulating the issue of alimony obligations was studied. The procedure for paying alimony for children, including voluntary payment and resolution of this issue in court, was considered. The authors draw attention to the judicial protection of the rights of the alimony claimant, which remains an effective way and contributes to the real protection of the child’s subjective right to alimony.The ways in which parents fulfill their obligations to maintain a child are emphasized: alimony is awarded as a share of the child’s mother’s or father’s income or as a fixed amount of money at the choice of one of the parents or other legal representatives with whom the child lives.The article analyzes the judicial procedure for consideration and resolution of cases on recovery of alimony in the course of simplified legal proceedings to ensure the fulfillment of parental obligations. The authors focus on the subject matter of proof in these cases and the documents to submit to the court and the enforcement authorities.The procedure for recovery of alimony according to the rules of writ proceedings in civil proceedings is characterized. The authors consider the positions of scholars and practitioners who have studied alimony relations in Ukraine. The article focuses on the advantages and disadvantages of alimony recovery through simplified claim and writ proceedings.The analysis of alimony obligations during martial law was carried out. Problematic issues that may arise in the course of alimony recovery during this period are outlined. The issue of the functioning of courts on certain territories of our country where active hostilities are taking place or the territory is occupied has been clarified; as well as the implementation of the «Electronic court» subsystem, etc. The article also highlights the issue of recovery of alimony from a person who lost his/her job during the war or is a military serviceman. The issue of the procedure for recovery of alimony if the payer is in another country is justified.The actions of the enforcement officer in case of child support arrears are specified. The responsibility of payers for late payment of alimony is noted.